Implementasi Building Information Modeling Dalam Perencanaan Struktur Rumah Susun Soekarno Hatta Semarang - widorini, trias (Jurnal Civil Engineering Study, 2023)
Construction digitization activities are very influential in supporting project work planning. So in planning, innovations are needed in order to achieve maximum results. The Ministry of PUPR issued PUPR Ministerial Decree No. 2018 concerning the Construction of State Buildings which requires the use of the Building Information Modeling method. Structural planning is very necessary to obtain a building that complies with the rules of the Indonesian National Standard. The structural planning of the Soekarno Hatta Semarang Flats refers to the regulations of the Indonesian National Standard (SNI), SNI 1726:2019 (Procedures for Planning Earthquake Resistance for Building and Non-Building Structures), SNI-03-1729-2019 (Structure Planning Procedures) Steel for Buildings), Loading Planning Regulations for Houses and Buildings 1987, I. Wahyudi (Charts and Tables for Reinforced Concrete Calculations). The structural planning of the Soekarno Hatta Semarang Flats includes the planning of the upper and lower structures. In planning the structure is modeled through SAP 2000 V.22 and Autodesk Revit 2022. The input loads are dead load, live load, wind load and earthquake load. The results of the planning use a combination of 32 earthquake loads. There are 7 types of beams, namely B64A, B67, B56A, B45A, B34A, B32A, and B22A. There are 3 types of columns, namely K88, K97, and K33A. There are 6 types of floor plates, namely S12A, S12A1, S12B, S12B1, S12C, and S12C1. As well as using a pile foundation with a diameter of 60 cm.